Effect of Antioxidant and Lipid Profile on the Coronary Heart Disease - Ahmad, Salman A; Al-Sayed, Raghda S (Al-Nahrain Journal of Science, 2018)
Despite the declining coronary heart disease (CHD) mortality rate, CHD remains a major cause of premature death. The present study connect the relationship between SOD (antioxidant enzyme), Lipid profile, Angina and Myocardial Infarction. To achieve this, collected 105 of patient with Angina and MI aged between (38-82) years, then measurement of superoxide dismutase (SOD) activity in sera of patients with Angina and MI. The results indicated moderated significant decreases of SOD levels (p